Cofactor-independent antiphospholipid antibodies activate the NLRP3-inflammasome via endosomal NADPH-oxidase: implications for the antiphospholipid syndrome - Müller-Calleja, Nadine; Köhler, Antonia; Siebald, Benjamin; Canisius, Antje; Orning, Carolin; Radsak, Markus; Stein, Pamela; Mönnikes, René; Lackner, Karl J. (Thrombosis and Haemostasis, 2015)
The antiphospholipid syndrome (APS) is an autoimmune disease characterised by thromboembolic events and/or pregnancy morbidity in the presence of antiphospholipid antibodies (aPL). Here we show that three cofactor independent human monoclonal aPL can induce transcription of NLRP3 and caspase-1 resulting in inflammasome activation specific for NLRP3. This depends fully on activation of endosomal NADPH-oxidase-2 (NOX2) by aPL. Activation of NOX2 and subsequent inflammasome activation by aPL are independent from TLR2 or TLR4. While endosomal superoxide production induces caspase-1 and NLRP3 transcription, it does not affect prae-IL-1β transcription. Therefore, release of IL-1β occurs only after activation of additional pathways like TLR7/8 or TLR2. All effects exerted by the monoclonal aPL can be reproduced with IgG fractions of APS patients proving that the monoclonal aPL are representative for the APS. IgG fractions of healthy controls or patients suffering from systemic lupus erythematosus have no effect. In a mouse model of the APS we can show inflammasome activation in vivo. Furthermore, mononuclear cells isolated from patients with the APS show an increased expression of caspase-1 and NLRP3 which is accompanied by a three-fold increased serum concentration of IL-1β suggesting chronic inflammasome activation in APS patients. In summary, we provide further evidence that endosomal NOX2 can be activated by cofactor independent aPL. This leads to induction of the NLRP3 inflammasome. Our data indicate that cofactor independent aPL might contribute significantly to the pathogenesis of the APS.
Keywords: Antiphospholipid syndrome; autoimmunity; monocytes; endosomal ROS generation; thrombosis